El impacto de la administración en la eficiencia del quehacer arquitectónico en las grandes empresas constructoras ubicadas en Morelia, Michoacán - Ventura Ruiz, Indira Citlalli (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
The sector of the construction industry as an economic indicator is complex and presents a series of specific characteristics that condition its existence, structure and functioning; thanks to strategic planning we can observe this phenomenon in the companies that operate in this market; On the other hand, there is a concern in Mexico to improve and harmonize information aimed at achieving better business management. Within a global vision, this thesis has the purpose of the impact of the administration on the efficiency of the architectural work of the large construction companies, in terms of their strategic planning. Specifically, conceptual and methodological aspects are delimited, the theory is synthesized on the matters that affect the object of study; the current situation of the construction sector in Mexico is analyzed, and the production functions of the construction companies are also estimated, by size and state individually and sectorially. This thesis raises how the administration supported by strategic planning impacts as a structured administrative tool within the ICT, quality, continuous improvement and benchmarking of human, material, economic and technological resources in the architectural work of companies builders with a multidimensional and multifunctional perspective aimed at planning, which overcomes the current limitations of financial, analytical and budgetary accounting, both at the level of activity as worker, product, area and company. The efficiency contemplates, not only the construction of the work and the company, but also the promotion of housing, budgets and commercial management. It is designed, developed and experienced in several companies, an integrated management model, based on a database management system and a computer application; the approach of the proposed model is multiuser, operational in real time and remote access, and scalable to be able to adapt to any situation and to any company.

El sector de la industria de la construcción como indicador económico, es complejo y presenta una serie de particularidades específicas que condicionan su existencia, estructura y funcionamiento; gracias a la planeación estratégica podemos observar este fenómeno en las empresas que operan en este mercado; por otra parte, existe una preocupación en México por mejorar y armonizar la información encaminada a realizar una mejor gestión empresarial. Dentro de una visión global, la presente tesis tiene como objeto el impacto de la administración en la eficiencia del quehacer arquitectónico de las grandes empresas constructoras, en cuanto a su planeación estratégica. Concretamente se delimitan aspectos conceptuales y metodológicos, se sintetiza la teoría sobre las materias que inciden en el objeto de estudio; se analiza la situación actual del sector de la construcción en México, y también se estiman las funciones de producción de las empresas constructoras, por tamaños y estados individual y sectorialmente. La presente tesis plantea de qué manera impacta la administración apoyada en la planeación estratégica como una herramienta administrativa estructurada dentro de las TICS, la calidad, mejora continua y el benchmarking de los recursos humanos, materiales, económicos y tecnológicos en el quehacer arquitectónico de las empresas constructoras con una perspectiva multidimensional y multifuncional encaminada a una planeación, que supera las limitaciones actuales de la contabilidad financiera, analítica y presupuestaria, tanto a nivel de actividad como de trabajador, producto, área y empresa. La eficiencia contempla, no solo la construcción de la obra y de la empresa, sino también la promoción de vivienda, los presupuestos y la gestión comercial.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2018-0077; Construcción; Gestión empresarial; Planeación estratégica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6145